SYSTEMATIC LITERATURE REVIEW OF BIM ASSESSMENT MODELS FOR BIM-BASED PROJECTS - Wan Nur Syazwani Wan Mohammad (International Journal of Accounting, Finance and Business, 2022)
Building Information Modeling (BIM) is an important technology enabler for digital transformation in construction. It is a highly collaborative process that allows architects, engineers, contractors and other construction professionals to plan, design and construct a building or facility in the form of a 3D model-base. Recently, various BIM assessment models have been established either from developed and developing countries to assess the BIM performance for construction professionals and BIM-based projects. Nevertheless, the adoption level of BIM among construction professionals in developing countries, particularly Malaysia remains lower than expected. Hence, the aim of this paper is to explore the BIM assessment model either from developed and developing countries via Systematic Literature Review (SLR). Subsequently, it is to determine the trends and key elements from the identified models. A Systematic Literature Review (SLR) was conducted on BIM assessment model articles published in three databases (i.e., Web of Science, Science Direct and Scopus) from 2007 until 2019. The results revealed that BIM assessment models from developed countries were dominant compared to developing countries. These models also vary according to their assessment framework and evaluation mechanisms. Other than that, the results also highlighted four (4) main elements from the BIM assessment models. These are; BIM objectives, BIM uses, BIM adoption components and project performance criteria’s’. Thus, the study provides a positive insight of the practitioners either from developed and developing countries to be considered in the trends and key elements while assessing BIM in their projects.